2010
DOI: 10.1597/08-268.1
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Abnormalities of Number and Position in the Permanent Dentition of Patients with Complete Bilateral Cleft Lip and Palate

Abstract: Patients with cleft lip and palate presented high prevalence of hypodontia and supernumerary teeth. The prevailing characteristics of their location may suggest the presence of a similar genetic component for the occurrence of hypodontia and cleft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
4
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 20 publications
6
28
4
3
Order By: Relevance
“…This result was close to some previous reports in Japanese CL/P subjects: 5.9% (Matsuo et al, 1987) and 6.0% (Tomizawa, 1989); but it was lower than other reports: 16.7% (Aljamal et al, 2010) and 11.7% (Tereza et al, 2010).…”
Section: Supernumerary Teeth In Cl/p Subjectssupporting
confidence: 90%
See 2 more Smart Citations
“…This result was close to some previous reports in Japanese CL/P subjects: 5.9% (Matsuo et al, 1987) and 6.0% (Tomizawa, 1989); but it was lower than other reports: 16.7% (Aljamal et al, 2010) and 11.7% (Tereza et al, 2010).…”
Section: Supernumerary Teeth In Cl/p Subjectssupporting
confidence: 90%
“…On the other hand, the prevalence of hypodontia in the permanent dentition of the CL/P subjects was much more frequent (52.7%) in this study, which was similar to rates reported in previous studies: 47.5% (Slayton et al, 2003), 49.8% , 51.1% (Watanabe et al, 2011), and 56.9% (Kadono et al, 2008). The prevalence in this study was relatively lower than that in some previous studies: 63% (Matern et al, 2012), 66.3% (Ohya et al, 1995), 66.7% (Aljamal et al, 2010), 67.6% (Aizenbud et al, 2005), 68.2% (Mori et al, 2005), 77% (Shapira et al, 2000), and 70.2% (Tereza et al, 2010). The finding that the prevalence of hypodontia was lower in primary dentition but higher in permanent dentition was reported in * There was a significant difference in prevalence between the cleft side (C) and the noncleft side (NC).…”
Section: Hypodontiacontrasting
confidence: 72%
See 1 more Smart Citation
“…2 Considerable interest has lately been shown in investigating this possibility, and a number of reports are appearing in the literature that bolster the evidence that this is an important line of investigation. A recent Brazilian study 3 reporting on evaluation of treatment records and panoramic films of 205 individuals with BCLP in an analysis of the location of tooth abnormalities and of the alveolar cleft concluded that the study provided evidence that suggests a common genetic component for the occurrence of hypdontia and cleft. Another recent study that sought to investigate dental clinical aspects that could serve to define subphenotypes of oral clefts included 65 families with 2 or more siblings born with clefts and 30 control families without individuals with clefts.…”
Section: Commentary and Analysismentioning
confidence: 99%
“…In addition to skeletal discrepancies, this deformity is often accompanied by dental abnormalities, such as hypodontia, hyperdontia, and transpositions (4,5). Its incidence in Asian population is reported to be around 2.0/1000 live births or higher (6).…”
Section: Introductionmentioning
confidence: 99%